Hashimoto’s thyroiditis is associated with reduced invasiveness in papillary thyroid carcinoma: a propensity score-matched retrospective cohort study - Li, Rui; Sun, Xu; Hu, Liai; Yu, Zhiyuan; Liu, Na; Li, Peiyu; Zhao, Xudong; Liang, Wenquan (Frontiers in Immunology, 2026)
BackgroundPapillary thyroid cancer (PTC), the predominant histologic subtype of thyroid cancer cases, has increased substantially over the past decades. In previous studies, Hashimoto’s thyroiditis (HT) exerts a paradoxical dual role in PTC. However, limited studies have specifically examined the association between HT and the invasion of PTC.MethodsIn this retrospective study, 10329 PTC patients were selected, and the clinicopathological features were retrospectively analyzed. Propensity score matching (PSM) was employed to minimize confounding effects from baseline variables. Univariate analysis and multivariate analysis were performed using binary logistic regression to determine the predictive factor. Odds ratio (OR) and 95% confidence interval (CI) were calculated.ResultsAmong 10329 PTC patients, 992 (9.6%) individuals were diagnosed with HT. Compared to the non-HT group, the HT group demonstrated lower rates of extrathyroidal extension (p<0.001), reduced multifocality (p=0.004), decreased bilateral carcinoma involvement (p<0.001), and a greater proportion of pathological N0 stage tumors (p=0.003). Following PSM, a cohort of 970 patients with HT and 2783 non-HT controls without HT were analyzed. HT was significantly associated with lower rates of: central lymph node metastasis (CLNM) in cN0 patients (p<0.001); lateral lymph node metastasis (LLNM) in cN1b patients (p=0.008); and bilateral carcinoma detection in patients with clinically unilateral PTC lesions (p=0.001).ConclusionThis study found an association between HT and reduced invasiveness of PTC, as evidenced by increased node-negative disease and reduced bilateral pathological involvement.